Ceramic composite diaphragm as well as manufacturing method and application thereof
By preparing a nano-ceramic composite membrane of rare earth oxides, metal-organic framework materials and hyperbranched polysilazane resin, the problems of thermal stability, mechanical strength and ion conductivity of sodium ion battery membranes in high temperature environments were solved, and the safety and long cycle life of the battery were achieved.
Patent Information
- Application Number
- CN202510827568.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-10-03
AI Technical Summary
Existing sodium-ion battery separators have poor thermal stability, limited mechanical strength, insufficient ion conductivity, and poor matching with the electrode interface under high-temperature environments, which affects the safety and cycle life of the battery.
Rare earth oxides, metal-organic framework materials and glass powder are mixed with hyperbranched polysilazane resin, and nano-ceramic fiber membranes are prepared by electrospinning, UV cross-linking and plasma treatment to form ceramic composite membranes with high porosity, high temperature resistance, high tensile strength and high ionic conductivity.
The high temperature resistance, mechanical strength and ion conductivity of the sodium ion battery separator have been improved, ensuring the safety and long cycle life of the battery in high temperature environments, and meeting the fast charging cycle test requirements of the new national standard.
Smart Images

Figure CN120749340A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of power battery diaphragms, and specifically relates to a high-temperature-resistant, highly safe, and long-life cycle ceramic composite diaphragm, and a manufacturing method and application thereof. Background Art
[0002] With the transformation of the global energy structure and the urgent demand for renewable energy, the application of electric vehicles and energy storage systems is becoming increasingly widespread, which has prompted the continuous advancement of battery technology. Among them, sodium-ion batteries, with their advantages of abundant resources and low cost, are gradually becoming a strong competitor to lithium-ion batteries. But at the same time, their safety issues, especially thermal stability and flame retardancy in high temperature environments, have become the focus of industry attention. Moreover, the technical requirements of sodium-ion battery separators need to integrate multiple aspects such as ion transmission efficiency, safety and chemical stability. Its core differences compared with lithium battery separators are as follows: 1. Pore size and porosity The radius of sodium ions (0.102nm) is more than 30% larger than that of lithium ions (0.076nm). Therefore, the separator requires a larger pore size (0.03-0.3μm) and a higher porosity (40%-50%), and the pores are evenly distributed to ensure efficient sodium ion transmission. The pore size of lithium battery separators is usually smaller and only adapts to the size characteristics of lithium ions. 2. Mechanical strength and safety Sodium dendrites are easier to grow and have high hardness. The diaphragm needs stronger puncture resistance (200-500gf) and mechanical strength (tensile strength ≥1400kgf / cm 2 ) to prevent short circuits. Although lithium battery separators need to be resistant to lithium dendrites, sodium batteries have more stringent requirements on the mechanical properties of separators. 3. Sodium battery separators need to be resistant to high temperatures (preferably >200°C). In order to avoid melting and evaporation of the separator at high temperatures, the higher the high temperature resistance of the separator, the better. 4. Chemical stability Sodium battery electrolytes (such as sodium hexafluorophosphate) are more corrosive, and the separator needs to remain stable during long-term immersion to avoid side reactions with the electrolyte. 5. Wettability and thermal stability Sodium battery separators need to optimize surface wettability. Therefore, sodium ion battery separators have higher requirements than lithium battery separators in pore size design, mechanical strength, high temperature resistance, wettability and chemical compatibility.
[0003] Furthermore, as a key component in batteries, battery separators not only separate the positive and negative electrodes to prevent short circuits, but more importantly, they must possess excellent ionic conductivity and heat and flame retardancy. While traditional polyolefin-based separators offer certain cost advantages, their thermal stability and electrolyte wettability are suboptimal, significantly limiting the application of sodium-ion batteries in high-temperature or extreme conditions. Furthermore, according to the "Safety Requirements for Power Batteries for Electric Vehicles" (GB38031-2025), the new national standard will take effect on July 1, 2027. Notably, this new national standard, for the first time in the world, requires that batteries "do not ignite or explode after thermal runaway due to an internal short circuit." Furthermore, the new national standard adds a "bottom impact test," which primarily assesses the battery's ability to withstand impact. The test method involves three impacts with a 30mm diameter impactor and 150j of energy. The technical requirement is that the battery "does not leak, exhibit casing rupture, ignite, or explode, and meet insulation resistance requirements." This test primarily examines the safety of power batteries after long-term fast-charging cycles. The test targets battery cells that are charged from 20% SOC to 80% SOC in a total charge time of no more than 15 minutes. The new national standard requires an external short-circuit test after 300 fast-charging cycles, ensuring no fire or explosion.
[0004] With the advancement of materials science, researchers have begun to explore new diaphragm materials in order to improve the safety performance of sodium-ion batteries. In terms of polymer material modification, inorganic nanoparticle filling, and the development of composite materials. For example, Patent Document 1 (CN202210225365.9) discloses a heat-resistant and flame-retardant composite diaphragm, its manufacturing method and application, etc., by introducing flame-retardant elements or groups into modified polymer materials (such as polyolefins, polyesters, etc.) to improve the flame retardant properties of the material. At the same time, the filling of inorganic nanoparticles such as alumina and silica can not only enhance the mechanical strength of the diaphragm, but also improve its thermal stability. In addition, modification and optimization of specific types of diaphragms is also one of the technical paths for the development of new diaphragm materials. For example, polyolefin composite diaphragms are modified by blending, grafting, etc. to improve their heat resistance and flame retardancy. By changing the composition and structure of glass fibers, their performance is further improved. By selecting high-performance polymer materials and optimizing the manufacturing process, the comprehensive performance of the diaphragm is improved. For example, Patent Document 2 (CN201611196385.9) discloses the use of a ceramic precursor solution coated with a polymer nanofiber membrane to prepare a battery separator, which can improve heat resistance and ion permeability. However, this method only forms a separator layer on the surface of the nanofibers; the substrate remains a polymer nanofiber membrane, potentially limiting long-term stability under extreme high temperatures. The improved mechanical properties rely on the ceramic layer filling the interstices between the fibers, without significantly improving strength. Despite numerous achievements in developing heat-resistant and flame-retardant sodium-ion battery separators both domestically and internationally, several challenges and problems remain. For example, existing technologies face bottlenecks stemming from insufficient separator performance. As a key component of sodium-ion batteries, the performance of the separator significantly impacts the overall performance of the battery. Currently, conventional sodium-ion battery separators suffer from the following major issues: 1) Poor thermal stability: At temperatures above 300°C, conventional separators are prone to thermal shrinkage, leading to internal short circuits and safety concerns. This inadequate separator thermal stability can severely impact battery safety and reliability, particularly when the battery is overcharged, over-discharged, or at high ambient temperatures. 2) Limited mechanical strength: During the charge and discharge process of sodium-ion batteries, the electrode materials will expand and contract in volume, which will produce certain mechanical stress on the diaphragm. The mechanical strength of traditional diaphragms is low, and it is difficult to withstand the volume changes of electrode materials, which can easily lead to diaphragm rupture and cause internal short circuits in the battery. 3) The ion conductivity performance needs to be improved: The pore structure and surface properties of traditional diaphragms have certain obstacles to the conduction of sodium ions, resulting in low sodium ion transmission efficiency in the diaphragm, affecting the battery's charge and discharge rate and cycle performance. In addition, the traditional diaphragm has insufficient lyophilicity and poor wettability of the electrolyte in the diaphragm, which will further reduce the ion conductivity performance. 4) Poor interface matching between the diaphragm and the electrode: The performance of sodium-ion batteries depends not only on the performance of the diaphragm and electrode materials themselves, but is also closely related to the interface matching between the diaphragm and the electrode.Currently, some existing separators and electrode materials differ significantly in chemical composition and physical structure, resulting in poor interfacial compatibility. During battery charge and discharge, charge accumulation and ion transport resistance easily occur at the interface, affecting the battery's electrochemical performance. Furthermore, during long-term battery operation, the interface between the separator and electrode exhibits poor stability, making interfacial side reactions more likely to occur. These side reactions can reduce the activity of the electrode material and the performance of the separator, further impacting the battery's cycle life and safety. Summary of the Invention
[0005] In order to overcome the technical problems of existing sodium ion battery separators, such as poor thermal stability, limited mechanical strength, ion conductivity that needs to be improved, and poor matching with the electrode interface, the present invention provides a ceramic composite separator for sodium ion batteries, a manufacturing method, and an application thereof.
[0006] A first aspect of the present invention provides a method for manufacturing a ceramic composite diaphragm, the method comprising the following steps:
[0007] (1) mixing at least two of a rare earth oxide, a metal organic framework material, and a glass powder, a polysilazane resin, and an organic solvent to obtain a precursor slurry, wherein the polysilazane resin comprises a hyperbranched polysilazane resin;
[0008] (2) electrospinning the precursor slurry to obtain a precursor film;
[0009] (3) The precursor film is sequentially subjected to ultraviolet cross-linking, plasma treatment and curing treatment to obtain the ceramic composite diaphragm.
[0010] In the present disclosure, at least two of rare earth oxides, metal organic framework materials and glass powders are selected, mixed with hyperbranched polysilazane resins and then electrostatically spun to form a precursor membrane. The hyperbranched polysilazane resin forms a nano-ceramic fiber membrane with certain strength and toughness during subsequent ultraviolet crosslinking, plasma treatment and curing treatment. Moreover, rare earth oxides and metal organic framework materials are embedded in the nano-ceramic fiber membrane, significantly improving the temperature resistance limit. The addition of rare earth oxides can further optimize the physicochemical properties of the material. For example, the added rare earth elements such as lanthanum (La) or cerium (Ce) can significantly improve the mechanical strength and ionic conductivity of the material. The metal organic framework material has a highly ordered porous structure and an adjustable chemical composition, which can provide an efficient channel for the transmission of sodium ions. Finally, a ceramic composite diaphragm with high porosity, high temperature resistance limit, high tensile strength and high ionic conductivity is obtained.
[0011] Preferably, the polysilazane resin further comprises at least one of a perhydropolysilazane resin, a polyborosilazane resin, a polyaluminosilazane resin, a polyzirconium silazane resin, and a polytitanium silazane resin, or a combination thereof, more preferably a combination of a hyperbranched polysilazane resin, a polyborosilazane, and a polyaluminosilazane.
[0012] Preferably, the structural formula of the hyperbranched polysilazane resin is:
[0013] wherein n=3 to 240, preferably n=60 to 240;
[0014] and / or, the average molecular weight of the hyperbranched polysilazane resin is 2,000 to 200,000, preferably 10,000 to 200,000, more preferably 50,000 to 200,000;
[0015] And / or, the hyperbranched polysilazane resin, as measured by TG / DSC, is heated to 1350° C. at a rate of 5-20° C. / min under a nitrogen atmosphere, and has a total weight loss rate of ≤30 wt % at ≤700° C., and a weight loss rate of ≤5 wt % between 700° C. and 1350° C.
[0016] Preferably, the rare earth oxide is selected from at least one of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, and Gd2O3, or a combination thereof, preferably at least two or at least three of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, and Gd2O3;
[0017] and / or, the content of rare earth oxide in the precursor slurry is 0.1 to 1.2 wt %, preferably 0.5 to 1.2 wt %;
[0018] And / or, the average particle size of the rare earth oxide is 10 nm to 100 nm.
[0019] Preferably, the metal organic framework material is at least one of silicon nanorods @ SWCNT core-shell MOF structural material, MIL-101 material (chromium-based MOF), UiO-66 (zirconium-based MOF), MOF-74 (magnesium-based MOF) and MOF-5 (zinc-based MOF), or a combination thereof;
[0020] And / or, the average particle size of the metal organic framework material is 100 nm to 300 nm;
[0021] And / or, the content of the metal organic framework material in the precursor slurry is 3-8 wt %.
[0022] More preferably, the diameter of the SWCNT in the silicon nanorod@SWCNT core-shell MOF structure material is 80±5 nm, and the thickness of the silicon nanorod shell is 10 nm;
[0023] The specific surface area of the MIL-101 material is 3000m 2 / g, and the pore size is 2 to 3 nm.
[0024] Preferably, the glass powder is selected from at least one of low-temperature glass powder, medium-temperature glass powder and high-temperature glass powder, or a combination thereof;
[0025] And / or, the content of glass powder in the precursor slurry is 3-8 wt%;
[0026] Preferably, the glass powder is nano glass powder, and more preferably the particle size of the nano glass powder is 50 to 500 nm;
[0027] Preferably, the melting point of the low-temperature glass powder is 500-600°C, the melting point of the medium-temperature glass powder is >600-800°C, and the melting point of the high-temperature glass powder is >800°C-1300°C.
[0028] Preferably, the viscosity of the precursor slurry is 350±20 cP (25° C.), and the Zeta potential is >+30 mV;
[0029] And / or, the content of the polysilazane resin in the precursor slurry is 25 to 75 wt %, preferably 25 to 55 wt %, and preferably 35 to 50 wt %.
[0030] Preferably, the electrospinning is carried out under the following conditions: the propulsion speed of the precursor slurry is 0.5-2.0 mL / h, the voltage is 15-25 kV, the distance between the electrospinning receiving device and the nozzle is 10-20 cm, the ambient temperature is 20-30° C., and the relative humidity is 30%-50%.
[0031] Preferably, the precursor membrane is a nanofiber membrane formed by three-dimensional interweaving of nanofibers, and the diameter of the nanofibers is 60 to 800 nm, preferably 150±20 nm.
[0032] Preferably, the UV crosslinking comprises: immersing the precursor film in a crosslinking agent solution, taking it out and drying it, and then irradiating it with UV light to obtain a crosslinked precursor film;
[0033] Preferably, the crosslinking agent in the crosslinking agent solution is selected from at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate and pentaerythritol tetraacrylate, or a combination thereof;
[0034] Preferably, the wavelength of the ultraviolet light irradiation is 200nm to 370nm, preferably 222nm or 254nm, the power is 10 to 30W, and the irradiation time is 10 to 80 minutes; more preferably, the irradiation is first performed at a wavelength of 254nm and a power of 10 to 20W for 20 to 30 minutes, and then at a wavelength of 222nm and a power of 10 to 20W for 20 to 30 minutes. The crosslinking agent used in the present invention is an ultraviolet light crosslinking agent. If it is directly added to the precursor slurry, it is not conducive to the formation of the precursor film.
[0035] In the present invention, after the ultraviolet cross-linking treatment is completed, the chemical bond formation reaction inside the precursor film is the key link to further improve its performance. Ultraviolet light irradiation causes the cross-linking agent molecules to react with the active groups in the polysilazane multi-element series material to form a stable chemical bond network structure. For example, the double bond in divinylbenzene (DVB) is opened under the action of ultraviolet light, and a cross-linking reaction occurs with the silicon-oxygen bond (Si-O) in the polysilazane multi-element series material to generate a cross-linked network with higher mechanical strength and chemical stability. This process not only enhances the high temperature resistance of the fiber membrane, but also improves its ion conductivity, making it more suitable for sodium ion battery separators.
[0036] Preferably, the plasma treatment is performed under the following conditions: power of 50 to 100 W, gas pressure of 0.1 to 0.5 Pa, and time of 10 to 20 minutes.
[0037] Preferably, the curing treatment is carried out under the following conditions: temperature of 150-800°C and time of 6-10 hours; preferably, the curing treatment includes: first keeping warm at 150-200°C for 1-2 hours, then keeping warm at 250-300°C for 2-3 hours, then keeping warm at 350-400°C for 1-4 hours, and finally optionally keeping warm at >400°C-600°C for 2-3 hours.
[0038] In the present invention, a gradient curing treatment is preferred. Specifically, during the gradient curing process, the polysilazane multi-element series resin material in the precursor film will gradually solidify to form a stable ceramic phase, while forming a tight composite structure with the MOF material. Moreover, the present invention can also effectively avoid the internal stress generated by the fiber membrane during the curing process due to rapid temperature changes through the gradient low-temperature curing treatment, thereby ensuring the structural integrity and performance stability of the fiber membrane. Among them, keeping warm at >400℃~600℃ for 2~3 hours is more conducive to the ceramic crystallization of the hyperbranched polysilazane resin.
[0039] Preferably, the method further comprises a step (4) after step (3): subjecting the ceramic composite diaphragm to laser cracking treatment or microwave curing treatment; the atmosphere of the laser cracking treatment is a non-oxidizing atmosphere, preferably a vacuum atmosphere or an inert atmosphere.
[0040] The second aspect of the present invention provides a ceramic composite membrane, which is a nano-ceramic fiber membrane. The nano-ceramic fiber membrane is three-dimensionally interwoven with nano-ceramic fibers composed of at least two of rare earth oxides, metal-organic framework materials and glass powders and a ceramic phase, wherein the rare earth oxides and glass powders are dispersed in the ceramic phase, and the metal-organic framework material and the ceramic phase form a composite structure; preferably, the ceramic phase is formed by a cross-linking reaction of a polysilazane resin and a cross-linking agent, and more preferably, the ceramic phase contains at least one of SiCN, Si3N4, SiC or a combination thereof.
[0041] Preferably, the diameter of the nano-ceramic fibers in the ceramic composite diaphragm is 50 to 600 nm;
[0042] And / or, the content of the ceramic phase is 60-80 wt %, more preferably, the amorphous ceramic phase in the ceramic phase accounts for 60%-100% of the total mass of the ceramic phase;
[0043] and / or, the content of the rare earth oxide is 1 to 3 wt %, preferably, the rare earth oxide is selected from at least one of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, Gd2O3 or a combination thereof, preferably a combination of Sc2O3, Sm2O3 and La2O3;
[0044] And / or, the content of the metal organic framework material is 5 to 20 wt%, and the metal organic framework material is selected from at least one of silicon nanorods @ SWCNT core-shell MOF structural material, MIL-101 material, (chromium-based MOF), UiO-66 (zirconium-based MOF), MOF-74 (magnesium-based MOF) and MOF-5 (zinc-based MOF) or a combination thereof, preferably silicon nanorods @ SWCNT core-shell MOF structural material;
[0045] And / or, the content of the glass powder is 5 to 20 wt %, and the glass powder is selected from at least one of low-temperature glass powder, medium-temperature glass powder, and high-temperature glass powder, or a combination thereof; the glass powder is nano-glass powder, and more preferably, the particle size of the nano-glass powder is 50 to 500 nm; preferably, the melting point of the low-temperature glass powder is 500 to 600° C., the melting point of the medium-temperature glass powder is >600 to 800° C., and the melting point of the high-temperature glass powder is >800 to 1300° C.;
[0046] and / or, the cross-linking agent is selected from at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate, or a combination thereof;
[0047] And / or, the polysilazane resin comprises a hyperbranched polysilazane resin, and the polysilazane resin preferably further comprises at least one of a perhydropolysilazane resin, a polyborosilazane resin, a polyaluminosilazane resin, a polyzirconium silazane resin, and a polytitanium silazane resin, or a combination thereof, preferably a combination of a hyperbranched polysilazane resin, a polyborosilazane, and a polyaluminosilazane. The hyperbranched polysilazane resin is the above-mentioned hyperbranched polysilazane resin.
[0048] Preferably, the ceramic composite diaphragm satisfies one or more of the following characteristics:
[0049] The ceramic composite diaphragm has a temperature resistance limit of ≥390°C, preferably ≥410°C, with a shrinkage rate of no more than 1.5% as measured according to ISO 11359;
[0050] The ionic conductivity of the ceramic composite diaphragm measured according to ASTM D257 standard is ≥1.2 mS / cm, preferably ≥1.8 mS / cm;
[0051] The ceramic composite diaphragm has a tensile strength measured according to ASTM D638 of ≥170 MPa, preferably ≥200 MPa;
[0052] The porosity of the ceramic composite diaphragm measured according to ISO 9277 standard is 75-90%, preferably 80-90%;
[0053] The ceramic composite diaphragm has an operating temperature of -60°C to 1350°C.
[0054] A third aspect of the present invention provides a battery comprising the above-mentioned ceramic composite diaphragm.
[0055] Preferably, the battery includes a sodium ion battery, a lithium ion battery and a sulfur ion battery
[0056] More preferably, the sodium ion battery further comprises: a layered oxide positive electrode, a hard carbon negative electrode and an electrolyte.
[0057] A fourth aspect of the present invention provides the use of the above-mentioned ceramic composite diaphragm or the above-mentioned battery in energy storage power stations, aircraft, ships, and automobiles, which can prevent problems such as thermal runaway, fire and explosion of the battery.
[0058] Beneficial effects of the present invention;
[0059] The polysilazane multi-element resin material used in this invention, due to its unique chemical structure, exhibits excellent high-temperature resistance and chemical stability, making it a key base material for the preparation of high-performance sodium-ion battery separators. The resulting sodium-ion battery separator exhibits excellent high-temperature resistance, mechanical strength, and ionic conductivity, meeting the high power, high energy density, and long cycle life requirements of sodium-ion batteries.
[0060] The present invention adopts electrospinning to prepare a composite diaphragm with a microporous structure, which can improve the wettability of the electrolyte while maintaining the structural integrity at high temperatures to avoid the risk of thermal runaway.
[0061] The present invention achieves a performance balance in terms of pore size design, mechanical strength, high temperature resistance, wettability and chemical compatibility for sodium ion battery separators by adding at least two of rare earth oxides, metal organic framework materials and glass powder to a polysilazane resin with a specific composition. BRIEF DESCRIPTION OF THE DRAWINGS
[0062] Figure 1 This is a SEM image of the ceramic composite diaphragm prepared in Example 1.
[0063] Figure 2 Schematic diagram of the structure of a ceramic composite diaphragm according to one embodiment of the present invention. DETAILED DESCRIPTION
[0064] In order to better understand the present invention, the present invention is further described and explained below in conjunction with the accompanying drawings and specific embodiments, and such description and explanation should not be construed as imposing any limitation on the protection scope of the present invention.
[0065] In one embodiment of the present invention, the ceramic composite membrane is a nano-ceramic fiber membrane, the structure of which is Figure 2 As shown. The nano-ceramic fiber membrane is composed of nano-ceramic fibers three-dimensionally interwoven with at least one (preferably two or three) ceramic phases of rare earth oxides, metal organic framework materials and glass powders, wherein the rare earth oxides and optional glass powders are dispersed in the ceramic phase, and the optional metal organic framework material and the ceramic phase form a composite structure; preferably, the ceramic phase is formed by a cross-linking reaction between a polysilazane resin and a cross-linking agent, preferably comprising at least one of SiCN, Si3N4, SiC or a combination thereof. Moreover, since the hyperbranched polysilazane resin is heated to 1350°C at a rate of 5 to 20°C / min under a nitrogen atmosphere, the total weight loss rate is ≤30wt% when ≤700°C, and the weight loss rate between 700 and 1350°C is ≤5wt%, that is, the total weight loss rate when heated to 1350°C is ≤35wt%, and the composite membrane is formed into an amorphous ceramic phase. Moreover, the composite membrane is mainly composed of rare earth oxides, metal organic framework materials and glass powder in addition to the ceramic phase, so the composite membrane of the present invention will not burn or support combustion at least at 1350°C.
[0066] In one embodiment of the present invention, the diameter of the nano-ceramic fibers in the ceramic composite membrane is 50 to 600 nm, preferably 100 to 300 nm, and more preferably 100 to 200 nm.
[0067] In one embodiment of the present invention, the content of the ceramic phase is 60-80 wt%, preferably 70-80 wt%. Preferably, the amorphous ceramic phase in the ceramic phase accounts for 60%-100%, preferably 70-80% of the total mass of the ceramic phase.
[0068] In one embodiment of the present invention, the rare earth oxide is selected from at least one of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, and Gd2O3, or a combination thereof, preferably a combination of Sc2O3, Sm2O3, and La2O3. The average particle size of the rare earth oxide is 10 nm to 100 nm, and the content of the rare earth oxide is 1 to 3 wt%.
[0069] In one embodiment of the present invention, the glass powder is selected from at least one of low-temperature glass powder (melting point 500-600°C), medium-temperature glass powder (melting point >600-800°C) and high-temperature glass powder (melting point >800-1300°C), or a combination thereof. The glass powder is nano-glass powder, and more preferably, the particle size of the nano-glass powder is 50-500nm. For example, the glass powder is at least one of low-temperature co-fired ceramic glass powder (LTCC glass powder, whose particle size is 50-500nm) with a melting point of 500-600°C, or multi-layer dielectric ceramic capacitor glass powder (MLCC glass powder, whose particle size is 50-500nm) with a melting point >800-1300°C, or a combination thereof. The content of the rare earth oxide is 5-20wt%, preferably 10-20wt%.
[0070] In one embodiment of the present invention, the metal organic framework material is at least one of silicon nanorod @ SWCNT core-shell MOF structural material, MIL-101 material (chromium-based MOF), UiO-66 (zirconium-based MOF), MOF-74 (magnesium-based MOF) and MOF-5 (zinc-based MOF) or a combination thereof, preferably silicon nanorod @ SWCNT core-shell MOF structural material. The average particle size of the metal organic framework material is 100nm to 300nm. For example, the diameter of SWCNT in the silicon nanorod @ SWCNT core-shell MOF structural material is 80±5nm, and the thickness of the silicon nanorod shell is 10nm. The specific surface area of the MIL-101 material is 3000m 2 / g, and the pore size is 2-3nm. The content of the metal organic framework material is 5-20wt%, preferably 10-20wt%.
[0071] In one embodiment of the present invention, the mass ratio of the rare earth oxide to the metal organic framework material is (0.1-1.2):(3-8), preferably (0.5-1.2):(3-8).
[0072] In one embodiment of the present invention, the crosslinking agent is selected from at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate and pentaerythritol tetraacrylate, or a combination thereof.
[0073] In one embodiment of the present invention, the polysilazane resin comprises a hyperbranched polysilazane resin, preferably a blend of a hyperbranched polysilazane resin and at least one of a perhydropolysilazane resin, a polyborosilazane resin, a polyaluminosilazane resin, a polyzirconium silazane resin, and a polytitanium silazane resin, or a combination thereof, more preferably a combination of a hyperbranched polysilazane resin, a polyborosilazane, and a polyaluminosilazane.
[0074] In a preferred embodiment of the present invention, the structural formula of the hyperbranched polysilazane resin is:
[0075] n=3-240, preferably n=60-240.
[0076] In a preferred embodiment of the present invention, the hyperbranched polysilazane resin is heated to 1350° C. at a rate of 5-20° C. / min under a nitrogen atmosphere, and has a total weight loss rate of ≤30 wt % at ≤700° C., and a weight loss rate of ≤5 wt % between 700° C. and 1350° C., as measured by TG / DSC.
[0077] In one embodiment of the present invention, electrostatic spinning is used to manufacture a ceramic composite diaphragm, which specifically includes: preparation of a precursor slurry, electrostatic spinning, ultraviolet light cross-linking, plasma treatment and curing treatment.
[0078] In one embodiment of the present invention, the raw material ratio (mass percentage) of the precursor slurry includes: polysilazane resin: 25-75% (preferably 25-55%, more preferably 35-50%); rare earth oxide: 0-1.2% (preferably 0.1-1.2 wt %, more preferably 0.5-1.2%); glass powder: 0-8 wt %, preferably 3-8 wt %; metal-organic framework (MOF) material: 0-8 wt %, preferably 3-8%, wherein the content of at least two of the rare earth oxide, glass powder, and metal-organic framework is not zero; an organic solvent is used to adjust the precursor slurry to 100%. Specifically, the organic solvent includes a ketone solvent. Preferably, the ketone solvent includes at least one of N-methylpyrrolidone and acetone, or a mixture thereof. For example, the organic solvent is an N-methylpyrrolidone / acetone mixture (volume ratio 3:1).
[0079] In one embodiment of the present invention, the method for forming a hyperbranched polysilazane resin comprises the following steps in sequence (Note: Me represents methyl CH3-, and vinyl represents vinyl CH2=CH-):
[0080] Step 1: Add 1 mole of potassium hydride (KH) to a suspension of 1 mole of commercially available 1,1,3,3-tetramethyl-1,3-divinylsilazane HN(SiMe2vinyl)2 (CAS No. 7691-02-3) in diethyl ether, and stir the mixture at room temperature for about 3-4 hours. After filtering and evaporating the solvent, KN(SiMe2vinyl)2 is obtained by recrystallization from a hexane / benzene mixture to obtain colorless crystals in high yield, as shown below:
[0081] HN(SiMe2vinyl)2+KH→KN(SiMe2vinyl)2+H2
[0082] Step 2: At room temperature, 1 mole of Cl-SiMe2vinyl and 1 mole of KN(SiMe2vinyl)2 obtained in step 1 are mixed and stirred for 3-4 hours in tetrahydrofuran (THF). After filtering and evaporating the solvent, a white solid N(SiMe2vinyl)3 is obtained, as shown below:
[0083] KN(SiMe2vinyl)2+Cl-SiMe2vinyl→N(SiMe2vinyl)3+KCl
[0084] Step 3: Mix 1 mol of the product N(SiMe2vinyl) from Step 2 with 3 mol of H-SiMe2Cl, then add 0.1 mol of KARSTEDT catalyst (CAS No. 81032-58-8), and carry out a hydrosilylation reaction at 80±5°C with magnetic stirring for 6 h to obtain N(SiMe2CH2CH2SiMe2Cl)3, as shown below:
[0085] N(SiMe2vinyl)3+3H-SiMe2Cl→N(SiMe2CH2CH2SiMe2Cl)3
[0086] Step 4: Add 3 mol of KN(SiMe2vinyl)2 obtained in step 2 to 1 mol of the solution of the compound N(SiMe2CH2CH2SiMe2Cl)3 obtained in step 3, stir in tetrahydrofuran (THF) for 3-4 hours, filter and evaporate to remove the solvent to obtain a white solid product with the molecular structure: As shown below:
[0087]
[0088] Step 5: 1 mol of the product N(SiMe2vinyl) from step 4 was mixed with 6 mol of H-SiMe2Cl, and then 0.1 mol of KARSTEDT catalyst (CAS No. 81032-58-8) was added. The mixture was subjected to a hydrosilylation reaction at 80±5°C with magnetic stirring for 6 h to obtain a dendrimer compound with six -SiMe2Cl groups. As shown below:
[0089]
[0090] Step 6: 1 mol of the product from step 5 Add 6 mol of KN(SiMe2vinyl)2 obtained in step 2, mix and stir in tetrahydrofuran (THF) for 3-4 hours, filter and evaporate to remove the solvent to obtain a white solid product with the molecular structure:
[0091]
[0092] Repeat steps 5 and 6, i.e., in step 2m+1, mix 1 mole of the product obtained in step 2m (m≥3) with 3m moles of H-SiMe2Cl, then add 0.1m mole of KARSTEDT catalyst (CAS No.81032-58-8), and carry out a hydrosilylation reaction at 80±5°C under magnetic stirring for 6h to obtain a dendrimer compound with 3m -SiMe2Cl groups added. i.e., in step 2m+2, mix 1 mole of the product obtained in step 2m+1 (m≥3) with 3m moles of KN(SiMe2vinyl)2 obtained in tetrahydrofuran (THF) and stir for 3-4 hours, filter, and evaporate to remove the solvent to obtain a white solid product. Repeat steps 5 and 6 several times until the molecular weight reaches 2000-200,000, preferably 10,000-200,000, and more preferably 50,000-200,000, and the molecular structure is:
[0093] n=3-240, preferably n=60-240.
[0094] In one embodiment of the present invention, the raw materials for the precursor slurry are weighed and mixed, and then ultrasonic dispersion grinding is used to obtain the precursor slurry. The ultrasonic frequency of the ultrasonic dispersion grinding is set in the range of 20 to 40 kHz, and the power density is preferably 0.5 W / cm 3The ultrasonic probe was immersed 5 to 10 cm below the liquid surface of the mixture. The ultrasonic dispersion and grinding equipment was a nano sand mill (0.3 mm ZrO2 grinding beads). The ultrasonic dispersion equipment was started, and the grinding device was turned on at the same time. The precursor slurry was grinded at 1500 rpm for 2 hours to obtain the precursor slurry. The viscosity of the obtained precursor slurry was 350 ± 20 cP (25 ° C), and the Zeta potential was greater than + 30 mV. During the ultrasonic dispersion and grinding process, the cavitation effect of the ultrasonic wave can effectively further disperse the rare earth elements in the polysilazane multi-element series material to form a uniform nano-scale dispersion system.
[0095] In one embodiment of the present invention, the precursor slurry is loaded into a syringe and connected to the nozzle of an electrostatic spinning device. The propulsion speed of the syringe pump is adjusted to 0.5-2.0 mL / h, the voltage of the high-voltage power supply of the electrostatic spinning device is 15-25 kV, the distance between its receiving device and the nozzle is 10-20 cm, the ambient temperature of the electrostatic spinning is 20-30 ° C, and the relative humidity is 30%-50%. Preferably, after electrostatic spinning is completed, the formed nanofiber membrane is collected and preliminarily processed (such as cleaning and drying). Specifically, a conveyor belt is connected by an easy demoulding substrate, passes through a UV ultraviolet curing zone, and most of the organic solvent is removed while curing. Subsequently, the automatic conveyor belt enters a plasma low-temperature gradient curing zone, enters a laser area by an automatic conveyor belt, removes residual organic solvent, and forms an amorphous inorganic ceramic fiber membrane, such as a three-dimensional interwoven nanofiber ceramic membrane with a diameter of 150 ± 20 nm.
[0096] In one embodiment of the present invention, a crosslinker and a solvent are mixed to prepare a crosslinker solution. The crosslinker includes, but is not limited to, at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate, or a combination thereof. The solvent includes, but is not limited to, ethanol. As an example, divinylbenzene and ethanol are mixed in a 1:10 volume ratio and stirred at 50-600 rpm for 30-60 minutes to prepare the crosslinker solution.
[0097] In one embodiment of the present invention, the three-dimensional interwoven nanofiber membrane is immersed in a prepared cross-linking solution and soaked for 10 to 20 minutes to allow the cross-linking solution to fully penetrate into the internal structure of the fiber membrane. Subsequently, the soaked fiber membrane is taken out, and one end of the fiber membrane is gently clamped with tweezers to allow it to drain naturally and remove excess cross-linking solution. The fiber membrane is spread flat on a UV irradiation platform to ensure that the surface of the fiber membrane is flat and wrinkle-free. The wavelength of the UV irradiation device is adjusted to 254nm and the power is 10 to 20W. After the irradiation time is 20 to 30 minutes, the wavelength of the UV irradiation device is adjusted to 222nm and the power is 10 to 20W. After the irradiation time is 20 to 30 minutes, the cross-linking agent molecules undergo a cross-linking reaction under the action of UV light during the gradient UV irradiation process to form a stable chemical bond network structure, thereby further enhancing the mechanical strength and chemical stability of the fiber membrane.
[0098] In one embodiment of the present invention, a fiber membrane soaked in a cross-linking agent solution is placed in a plasma treatment device, the plasma power is adjusted to 50 to 100 W, the air pressure is 0.1 to 0.5 Pa, and the treatment time is 10 to 20 minutes. After the plasma treatment is completed, the fiber membrane is placed in a gradient low-temperature curing furnace and cured according to a preset temperature gradient. For example, the temperature of the curing treatment is 150 to 400 ° C, and the time is 6 to 9 hours. Preferably, the curing temperature gradient is: first keep warm at 150-200 ° C for 1-2 hours, then heat to 250-300 ° C and keep warm for 2-3 hours, finally heat to 350-400 ° C and keep warm for 3-4 hours, and finally optionally keep warm at 400 to 600 ° C for 2 to 3 hours to complete the curing, that is, the gradient ceramic composite diaphragm for sodium ion batteries of the present invention is obtained.
[0099] In summary, the high-strength ceramic composite diaphragm of the present invention can overcome the problems of poor thermal stability, mechanical strength, ion conductivity, and poor matching with the electrode interface of traditional isolation membranes.
[0100] The raw materials used in the following examples and comparative examples are as follows:
[0101] Preparation Example 1 of a hyperbranched polysilazane resin (average molecular weight of about 10,000, i.e., X1), the preparation process includes:
[0102] The method for producing a hyperbranched polysilazane resin comprises the following steps in sequence (Note: Me represents a methyl group CH3-, and vinyl represents a vinyl group CH2=CH-):
[0103] Step 1: Add 1 mole of potassium hydride (KH) to a suspension of 1 mole of commercially available 1,1,3,3-tetramethyl-1,3-divinylsilazane HN(SiMe2vinyl)2 (CAS No. 7691-02-3) in diethyl ether, and stir the mixture at room temperature for about 3-4 hours. After filtering and evaporating the solvent, KN(SiMe2vinyl)2 is obtained by recrystallization from a hexane / benzene mixture to obtain colorless crystals in high yield, as shown below:
[0104] HN(SiMe2vinyl)2+KH→KN(SiMe2vinyl)2+H2
[0105] Step 2: At room temperature, 1 mole of Cl-SiMe2vinyl and 1 mole of KN(SiMe2vinyl)2 obtained in step 1 are mixed and stirred for 3-4 hours in tetrahydrofuran (THF). After filtering and evaporating the solvent, a white solid N(SiMe2vinyl)3 is obtained, as shown below:
[0106] KN(SiMe2vinyl)2+Cl-SiMe2vinyl→N(SiMe2vinyl)3+KCl
[0107] Step 3: Mix 1 mol of the product N(SiMe2vinyl) from Step 2 with 3 mol of H-SiMe2Cl, then add 0.1 mol of KARSTEDT catalyst (CAS No. 81032-58-8), and carry out a hydrosilylation reaction at 80±5°C with magnetic stirring for 6 h to obtain N(SiMe2CH2CH2SiMe2Cl)3, as shown below:
[0108] N(SiMe2vinyl)3+3H-SiMe2Cl→N(SiMe2CH2CH2SiMe2Cl)3
[0109] Step 4: Add 3 mol of KN(SiMe2vinyl)2 obtained in step 2 to 1 mol of the solution of the compound N(SiMe2CH2CH2SiMe2Cl)3 obtained in step 3, stir in tetrahydrofuran (THF) for 3-4 hours, filter and evaporate to remove the solvent to obtain a white solid product with the molecular structure: As shown below:
[0110]
[0111] Step 5: 1 mol of the product N(SiMe2vinyl) from step 4 was mixed with 6 mol of H-SiMe2Cl, and then 0.1 mol of KARSTEDT catalyst (CAS No. 81032-58-8) was added. The mixture was subjected to a hydrosilylation reaction at 80±5°C with magnetic stirring for 6 h to obtain a dendrimer compound with six -SiMe2Cl groups. As shown below:
[0112]
[0113] Step 6: 1 mol of the product from step 5 Add 6 mol of KN(SiMe2vinyl)2 obtained in step 2, mix and stir in tetrahydrofuran (THF) for 3-4 hours, filter and evaporate to remove the solvent to obtain a white solid product with the molecular structure:
[0114]
[0115] Repeat steps 5 and 6, i.e., in step 2m+1, mix 1 mol part of the product obtained in step 2m (m≥3) with 3 mol parts of H-SiMe2Cl, then add 0.1 nm mol part of KARSTEDT catalyst (CAS No. 81032-58-8), and carry out hydrosilylation reaction at 80±5°C under magnetic stirring for 6 h to obtain a dendrimer compound with 3n -SiMe2Cl groups added. i.e., in step 2m+2, mix 1 mol part of the product obtained in step 2m+1 (m≥3) with 3 nm mol parts of KN(SiMe2vinyl)2 obtained in tetrahydrofuran (THF) and stir for 3-4 hours. After filtering and evaporating the solvent, a white solid product can be obtained. Repeat steps 5 and 6 four times to achieve a molecular weight of about 10,000.
[0116] Preparation Example 2 of a hyperbranched polysilazane resin (average molecular weight 69789, i.e., X2) comprises following the same preparation steps as in Preparation Example 1, but repeating steps 5 and 6 25 times, to achieve a molecular weight of approximately 70,000. X2, as measured by TG / DSC under a nitrogen atmosphere, exhibits a weight loss of ≤33 wt% when heated at 5°C / min to 1350°C, and ≤28 wt% when heated at 20°C / min to 1350°C.
[0117] Preparation Example 3 of a hyperbranched polysilazane resin (average molecular weight of about 100,000, i.e., X3) comprises the following steps: following the same preparation steps as in Preparation Example 1, but repeating steps 5 and 6 40 times, until the molecular weight reaches about 100,000.
[0118] Preparation Example 4 of a hyperbranched polysilazane resin (average molecular weight of about 150,000, i.e., X4) comprises the following steps: following the same preparation steps as in Preparation Example 1, but repeating steps 5 and 6 60 times, and the molecular weight reaches about 150,000.
[0119] Example 1
[0120] Step (1), preparation of a precursor slurry: a polysilazane resin (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) with a content of 40wt%, a rare earth oxide (mass ratio Sc2O3:Sm2O3:La2O3 = 1:2:3) with a content of 1.0wt%, a silicon nanorod @ SWCNT core-shell MOF with a content of 6wt%, a LTCC nanoglass powder (50-500nm) with a content of 6wt%, and the remainder being an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0121] Step (2), electrospinning: the precursor slurry obtained in step (1) is loaded into a syringe and connected to the nozzle of the electrospinning device. The propulsion speed of the injection pump is adjusted to 0.5-2.0 mL / h, the voltage of the high-voltage power supply of the electrospinning device is 15 kV, the distance between the receiving device and the nozzle is 15 cm, the ambient temperature of the electrospinning is 20-30 ° C, and the relative humidity is 30%-50%. After the electrospinning is completed, the formed nanofiber membrane is collected and preliminarily processed. The fiber membrane is carefully peeled off from the receiving device to avoid damage to the fiber structure. The peeled fiber membrane is placed in deionized water and soaked for 10-15 minutes to remove the residual organic solvent and unreacted impurities on the surface. Subsequently, the fiber membrane is rinsed with deionized water 3-5 times to ensure thorough cleaning. The cleaned fiber membrane is dried in an oven at 60-80 ° C for 2-3 hours to remove moisture and shape the fiber membrane to form a three-dimensional interwoven nanofiber membrane with a diameter of 150.
[0122] Step (2): UV cross-linking of fiber membrane
[0123] Mix divinylbenzene crosslinker and ethanol in a volume ratio of 1:10, and stir at 50-600 rpm for 30-60 minutes to prepare a crosslinker solution. Immerse the three-dimensional interwoven nanofiber membrane obtained in step (2) in the prepared crosslinker solution and soak for 10-20 minutes to allow the crosslinker solution to fully penetrate into the internal structure of the fiber membrane. Subsequently, take out the soaked fiber membrane, gently clamp one end of the fiber membrane with tweezers, let it drain naturally, and remove excess crosslinker solution. Spread the fiber membrane flat on the ultraviolet light irradiation platform to ensure that the surface of the fiber membrane is flat and wrinkle-free. Adjust the wavelength of the ultraviolet light irradiation device to 254nm and the power to 10-20W. After the irradiation time is 20-30 minutes, adjust the wavelength of the ultraviolet light irradiation device to 222nm and the power to 10-20W. The irradiation time is 20-30 minutes, so that during the gradient ultraviolet light irradiation process, the crosslinking agent molecules undergo a crosslinking reaction under the action of ultraviolet light to form a stable chemical bond network structure, further enhancing the mechanical strength and chemical stability of the fiber membrane.
[0124] Step (4), plasma treatment + gradient low-temperature curing: Place the fiber membrane treated in step (3) in a plasma treatment device, adjust the plasma power to 50-100W, the air pressure to 0.1-0.5Pa, and the treatment time to 10-20 minutes. After the plasma treatment is completed, place the fiber membrane in a gradient low-temperature curing furnace and perform gradient curing treatment according to a preset temperature gradient. The gradient curing temperature is: first keep warm at 150-200°C for 1-2 hours, then heat to 250-300°C and keep warm for 2-3 hours, and finally heat to 350-400°C and keep warm for 3-4 hours to complete the curing, and obtain the ceramic composite diaphragm for sodium ion batteries of the present invention. The temperature resistance of the ceramic composite diaphragm: the thermal shrinkage rate at 450°C is 0.8%.
[0125] Example 2
[0126] The method for manufacturing the ceramic composite diaphragm in Example 2 refers to that in Example 1, except that in step (1), the content of the rare earth oxide (Sc2O3:Sm2O3:La2O3=1:2:3) was reduced to 0.5 wt %. The other ratios were the same as in Example 1. The resulting ceramic composite diaphragm had a heat resistance of 1.5% at 430°C.
[0127] Example 3
[0128] The method for manufacturing the ceramic composite diaphragm in Example 3 refers to that in Example 1, except that in step (1), the silicon nanorods@SWCNT core-shell MOF is replaced with MIL-101 (specific surface area 3000m 2 / g), with other proportions being the same as in Example 1. The resulting ceramic composite diaphragm had a heat resistance of 0.9% at 445°C. Comparison of Example 1 and Example 3 shows that the change in MOF type has little effect on performance, with the core-shell structure being superior.
[0129] Example 4
[0130] The manufacturing method of the ceramic composite diaphragm in Example 4 refers to Example 1, except that: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 12000 ± 0.2 million, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 12000 ± 0.2 million, Al / Si molar ratio of 1:3) = 2:1:1)) content is 25 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 1.0 wt%, silicon nanorods @ SWCNT core-shell MOF content is 6 wt%, LTCC nano glass powder (50 ~ 500 nm) content is 6 wt%, the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0131] Example 5
[0132] The manufacturing method of the ceramic composite diaphragm in Example 5 refers to Example 1, except that: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 12000±0.2 million, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 12000±0.2 million, Al / Si molar ratio of 1:3) = 2:1:1)) content is 35 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 1.0 wt%, silicon nanorods @ SWCNT core-shell MOF content is 6 wt%, LTCC nano glass powder (50-500 nm) content is 6 wt%, and the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0133] Example 6
[0134] The manufacturing method of the ceramic composite diaphragm in Example 6 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: a polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 120,000 ± 20,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 120,000 ± 20,000, Al / Si molar ratio of 1:3) = 2:1:1)) content of 50 wt%, a rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content of 1.0 wt%, a silicon nanorod @ SWCNT core-shell MOF content of 6 wt%, a LTCC nanoglass powder (50 ~ 500 nm) content of 6 wt%, and the remainder being an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0135] Example 7
[0136] The manufacturing method of the ceramic composite diaphragm in Example 7 refers to Example 1, except that: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 12000 ± 0.2 million, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 12000 ± 0.2 million, Al / Si molar ratio of 1:3) = 2:1:1)) content is 55 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 1.0 wt%, silicon nanorods @ SWCNT core-shell MOF content is 6 wt%, LTCC nano glass powder (50 ~ 500 nm) content is 6 wt%, the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0137] Comparative Example 1
[0138] Formula and process of traditional polyolefin diaphragm:
[0139] Polyethylene (PE) raw materials (without functional additives) are made into polyolefin membranes through melt stretching. The resulting polyolefin membrane has a porosity of 45%, a temperature resistance of melting at 180°C, and a heat shrinkage of 12% at 150°C.
[0140] Table 1 shows the composition and properties of the ceramic composite diaphragms of Examples 1-7 (E1-E7) and the diaphragm of Comparative Example 1 (CE1):
[0141]
[0142] Comparing Example 4, Example 5, Example 1, Example 6, and Example 7, it can be seen that as the content of polysilazane resin in the precursor slurry increases, for example, comparing Example 4 (25%), 5 (35%), 1 (40%), 6 (50%), and 7 (55%), it can be seen that: (1) The thermal shrinkage rate (temperature resistance) decreases and the temperature resistance limit increases, mainly because the high polysilazane content enhances the stability of the cross-linked network. (2) Ionic conductivity: first increases and then decreases (1.5→2.0→2.3→2.5→2.4mS / cm), mainly because an appropriate amount of resin improves the stability of the MOF structure, and an excessive amount will block the pores. (3) Tensile strength increases linearly (200→240→255→265→270MPa), mainly because the resin provides mechanical support as a three-dimensional network skeleton. (4) Porosity: monotonically decreases (88%→83%→85%→80%→78%), mainly because the resin fills the pore space.
[0143] Example 8
[0144] The manufacturing method of the ceramic composite diaphragm in Example 8 refers to Example 1, except that: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%) mass ratio = 2:2) is 40 wt%, the content of rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0145] Example 9
[0146] The manufacturing method of the ceramic composite diaphragm in Example 9 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: the content of the hyperbranched polysilazane resin (X2, average molecular weight 69789) is 40 wt %, the content of the rare earth oxide (Sc2O3:Sm2O3:La2O3=1:2:3) is 10 wt %, the content of the silicon nanorods @ SWCNT core-shell MOF is 6 wt %, the content of the LTCC nanoglass powder (50-500 nm) is 6 wt %, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0147] Example 10
[0148] The manufacturing method of the ceramic composite diaphragm in Example 10 refers to Example 1, except that: Step (1), preparation of the precursor slurry: a polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (La2O3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0149] Example 11
[0150] The manufacturing method of the ceramic composite diaphragm in Example 11 refers to Example 1, except that: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (Sm2O3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0151] Example 12
[0152] The manufacturing method of the ceramic composite diaphragm in Example 12 refers to Example 1, except that: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X2, average molecular weight of 69789): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (Sm2O3:La2O3=1:1) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0153] Example 13
[0154] The manufacturing method of the ceramic composite diaphragm in Example 13 refers to Example 1, except that: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X3, average molecular weight of about 100,000): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (Sc2O3:Sm2O3:La2O3=1:2:3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0155] Example 14
[0156] The manufacturing method of the ceramic composite diaphragm in Example 14 refers to Example 1, except that: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X4, average molecular weight of about 150,000): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (Sc2O3:Sm2O3:La2O3=1:2:3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0157] Example 15
[0158] The manufacturing method of the ceramic composite diaphragm in Example 15 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: the content of the polysilazane resin matrix (hyperbranched polysilazane resin (X1, average molecular weight of about 10,000): polyborosilazane (average molecular weight of 10,000-15,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 10,000-15,000, Al / Si molar ratio of 1:3) mass ratio = 2:1:1) is 40 wt%, the content of rare earth oxide (Sc2O3:Sm2O3:La2O3=1:2:3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50-500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0159] Comparative Example 2
[0160] The manufacturing method of the ceramic composite diaphragm in Comparative Example 2 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: the content of polyborosilazane (average molecular weight of 10,000 to 15,000, boron content of about 5 wt%) is 40 wt%, the content of rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) is 1.0 wt%, the content of silicon nanorods @ SWCNT core-shell MOF is 6 wt%, the content of LTCC nanoglass powder (50 to 500 nm) is 6 wt%, and the balance is an organic solvent (NMP / acetone mixture (volume ratio 3:1)) 1.
[0161] Table 2 shows the composition and properties of the ceramic composite diaphragms of Examples 8-15 (E8-E15) and Comparative Example 2 (CE2):
[0162]
[0163] Figure 1 This is a SEM image of the ceramic composite diaphragm prepared in Example 1. It can be seen from the figure that it has an excellent porous structure.
[0164] Comparing Example 1, Example 8 and Example 9, it can be seen that the polysilazane resin contains a hyperbranched polysilazane resin. Compared with Comparative Example 1, the resulting ceramic composite diaphragm temperature resistance limit, ionic conductivity, tensile strength and porosity can be significantly improved. Among them, the tensile strength and temperature resistance limit of the composite diaphragm prepared by hyperbranched polysilazane resin+polyborosilazane+polyaluminosilazane in Example 1> the composite diaphragm prepared by hyperbranched polysilazane resin+polyborosilazane in Example 8> the composite diaphragm prepared by only one hyperbranched polysilazane resin in Example 9. Mainly because three kinds of polysilazane resins (hyperbranched polysilazane resin+polyborosilazane / polyaluminosilazane) are used in Example 1, the cross-linked networks of different resins are complementary, which significantly enhances the mechanical strength and thermal stability of the fiber membrane. Example 8 uses two resins (hyperbranched polysilazane resin+polyborosilazane) combination to form a cross-linked network structure, but the temperature resistance and tensile strength are lower than those in Example 1. Example 9 uses only a single resin (hyperbranched polysilazane resin). Although it has a cross-linked network structure, the cross-linked network is relatively simple, and its temperature resistance is lower than that of Example 8. Comparative Example 2, which uses only polyborosilazane, produces a composite membrane with far inferior temperature resistance and tensile strength to that of Example 9.
[0165] Comparing Example 1, Example 10, Example 11 and Example 12, it can be seen that the addition of rare earth oxides can achieve a significant improvement in the temperature resistance limit, ionic conductivity, tensile strength and porosity of the ceramic composite diaphragm compared to Comparative Example 1. Among them, the ionic conductivity, temperature resistance limit and tensile strength of the composite diaphragm prepared by using three rare earth composite oxides in Example 1 are greater than the composite diaphragm prepared by using two rare earth composite oxides in Example 12, and are greater than the composite diaphragms prepared by using one rare earth oxide in Examples 10 and 11. Example 1 uses three rare earth oxides (Sc2O3 / Sm2O3 / La2O3) and optimizes the ion transport path and thermal stability of the ceramic phase through lattice doping and defect regulation of different rare earth elements. Example 12 uses double rare earth (Sm2O3 / La2O3). Although it also uses lattice doping and defect regulation of different rare earth elements, its performance is not as good as that of Example 1. Examples 10-11 use only a single rare earth (La2O3 or Sm2O3), resulting in a single ion channel and its performance is inferior to that of Example 12.
[0166] Comparing Example 1, Example 13, Example 14 and Example 15, it can be seen that the composite membrane obtained by using a polysilazane resin made of a hyperbranched polysilazane resin with an average molecular weight of 3000 to 200,000 as a matrix can achieve significantly improved temperature resistance, ionic conductivity and tensile strength compared with Comparative Example 1. Among them, the temperature resistance, ionic conductivity and tensile strength of the composite membrane obtained in Example 15 of the polysilazane resin made of a hyperbranched polysilazane resin with an average molecular weight of only about 10,000 are not as good as those in Example 1, Example 13 and Example 14, as follows: (1) E15: 390℃ (significantly lower than E13: 455℃, E14: 460℃), high molecular weight resin (50,000 to 200,000) forms a more stable cross-linked network, inhibiting high temperature thermal shrinkage; low molecular weight resin has insufficient cross-linking density and reduced thermal stability. (2) E15: 1.3 mS / cm (significantly lower than E13: 2.4 mS / cm, E14: 2.5 mS / cm). High molecular weight resin optimizes the MOF / ceramic interface and promotes ion transport; low molecular weight resin leads to disordered pore structure, hindering ion migration. (3) E15: 170 MPa (significantly lower than E13: 260 MPa, E14: 265 MPa). High molecular weight resin provides stronger three-dimensional skeleton support; low molecular weight resin lacks mechanical strength, and the fiber network is easily broken. Although the porosity is higher (E15: 88% vs. E13: 78%), it cannot be converted into actual performance advantages due to insufficient resin cross-linking and pore structure defects.
[0167] Example 16
[0168] The manufacturing method of the ceramic composite diaphragm in Example 16 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin is X2, with an average molecular weight of 69789): polyborosilazane (average molecular weight of 120,000 ± 20,000, boron content of approximately 5 wt%): polyaluminosilazane (average molecular weight of 120,000 ± 20,000, Al / Si molar ratio of 1:3) = 2:1:1)) content is 40 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 0 wt%, silicon nanorods @ SWCNT core-shell MOF content is 6 wt%, LTCC nano glass powder (50 ~ 500 nm) content is 6 wt%, and the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0169] Example 17
[0170] The manufacturing method of the ceramic composite diaphragm in Example 17 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin is X2, with an average molecular weight of 69789): polyborosilazane (average molecular weight of 120,000 ± 20,000, boron content of approximately 5 wt%): polyaluminosilazane (average molecular weight of 120,000 ± 20,000, Al / Si molar ratio of 1:3) = 2:1:1)) content is 40 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 10 wt%, silicon nanorods @ SWCNT core-shell MOF content is 0 wt%, LTCC nano glass powder (50 ~ 500 nm) content is 6 wt%, and the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0171] Example 18
[0172] The manufacturing method of the ceramic composite diaphragm in Example 18 refers to Example 1, with the only difference being: Step (1), preparation of the precursor slurry: polysilazane resin matrix (hyperbranched polysilazane resin is X2, with an average molecular weight of 69789): polyborosilazane (average molecular weight of 120,000 ± 20,000, boron content of about 5 wt%): polyaluminosilazane (average molecular weight of 120,000 ± 20,000, Al / Si molar ratio of 1:3) = 2:1:1)) content is 40 wt%, rare earth oxide (Sc2O3: Sm2O3: La2O3 = 1:2:3) content is 10 wt%, silicon nanorods @ SWCNT core-shell MOF content is 6 wt%, LTCC nano glass powder (50 ~ 500 nm) content is 0 wt%, and the balance is organic solvent (NMP / acetone mixture (volume ratio 3:1)).
[0173] Table 3 shows the composition and properties of the ceramic composite diaphragms of Examples 16-18 (E16-18):
[0174] Precursor slurry composition E16 E17 E18 Polysilane resin / wt% 40 40 40 Rare earth oxides / wt% 0 1.0 1.0 MOF material / wt% 6 0 6 Glass powder / wt% 6 6 0 Diaphragm composition E16 E17 E18 Ceramic phase / wt% 70 80.0 80.0 Ratio of amorphous ceramic phase to ceramic phase / % 60 68 65% Rare earth oxides / wt% 0 2.9 2.9 MOF material / wt% 15 0 17.1 Glass powder / wt% 15 17.1 0 Average diameter of nano ceramic fibers / nm 150±8 150±8 150±8 Diaphragm characteristics E16 E17 E18 Temperature limit ℃ 400 425 390 Ionic conductivity 1.2 1.8 1.6 Tensile strength / MPa 180 230 210 Porosity / % 80 82 81
[0175] Comparing Examples 16-18, adding at least two of the rare earth oxides, metal organic framework materials, and glass powder can achieve a significant improvement in at least one of the temperature resistance limit, ionic conductivity, and tensile strength.
[0176] Comparing Example 1, Example 16, Example 17 and Example 18, it can be seen that Example 1, which combines rare earth oxides, MOF materials and glass powder, has significantly improved temperature resistance, ionic conductivity and tensile strength. Example 18, which does not add glass powder, has a lower porosity, ionic conductivity, tensile strength and temperature resistance than Example 1. Example 16, which does not add rare earth oxides, has lower temperature resistance and ionic conductivity than Example 1. Example 17, which does not add MOF materials, has the following problems: 1) The porosity is lower than that of Example 1 (CE3: 82%, E1: 85%), because MOF materials (such as silicon nanorods @ SWCNT core-shell MOF) have a high specific surface area and are key components for forming porous structures. The lack of MOF directly leads to a decrease in porosity. 2) The ionic conductivity is not as good as that of Example 1 (E17: 1.8mS / cm, E1: 2.3mS / cm). Since the regular pores provided by MOF can optimize the electrolyte wettability and lithium ion transmission path, its absence leads to a decrease in ion transmission efficiency. 3) The tensile strength is not as good as that of Example 1 (E17: 230MPa vs E1: 255MPa). Since the synergistic effect of core-shell MOF and polysilazane resin can enhance the mechanical strength of the fiber network, the absence of MOF weakens the structural support. 4) The temperature resistance limit is not as good as that of Example 1 (E17: 425℃, E1: 450℃). Since the nano-scale dispersion of MOF can inhibit the crystallization and shrinkage of the ceramic phase at high temperature, its absence leads to a partial decrease in thermal stability. Therefore, Example 17, which does not add MOF material, has a lower porosity, ionic conductivity, tensile strength and temperature resistance than Example 1. Therefore, it can be seen that the influence of MOF material on porosity and ionic conductivity is most direct, while the influence on mechanical properties and thermal stability is achieved through structural synergy.
[0177] Example 19
[0178] The preparation of the sodium ion battery in Example 19 includes:
[0179] (1) The positive electrode material (Na3V2(PO4)3), conductive agent (Super P) and binder (PVDF) were mixed in a mass ratio of 8:1:1 and coated on an aluminum foil current collector;
[0180] (2) The negative electrode is made of hard carbon material, mixed with a conductive agent and a binder in a mass ratio of 9:0.5:0.5, and then coated on copper foil;
[0181] (3) The composite diaphragm prepared in Example 1;
[0182] (4) injecting EC / DMC electrolyte containing 1 M NaPF6 (volume ratio 1:1);
[0183] (5) Assemble into button batteries and perform aging treatment.
[0184] The sodium ion battery obtained in Example 19 was subjected to high-power performance testing. The sodium ion battery using the composite separator of the present invention was charged and discharged at 1C, 2C, and 5C rates. The results showed that at a 5C rate, it could still maintain a capacity retention rate of more than 85%, demonstrating excellent high-power performance. Specific data are as follows:
[0185] 1C rate: initial discharge capacity is 150mAh / g,
[0186] 2C rate: discharge capacity is 145mAh / g (capacity retention rate 96.7%),
[0187] 5C rate: discharge capacity is 128mAh / g (capacity retention rate is 85.3%).
[0188] The sodium-ion battery obtained in Example 19 was subjected to high energy density testing. Through constant current charge and discharge testing, the battery's energy density at a 0.1C rate reached 400Wh / kg, significantly higher than the sodium-ion battery prepared with a traditional diaphragm (350Wh / kg). In addition, at a 1C rate, the energy density remained at 380Wh / kg, indicating that the composite diaphragm can effectively improve the energy density of the battery.
[0189] The sodium-ion battery obtained in Example 19 was subjected to a long cycle life test, with 1000 cycles at a 1C rate. The results showed that the sodium-ion battery using the composite separator of the present invention had a capacity retention rate of over 90%, and an average capacity decay rate of only 0.01% per cycle. Specific data are as follows:
[0190] Initial capacity: 150mAh / g,
[0191] Capacity after 500 cycles: 145mAh / g (capacity retention rate 96.7%),
[0192] Capacity after 1000 cycles: 135 mAh / g (capacity retention rate 90%).
[0193] The sodium ion battery obtained in Example 19 was subjected to high temperature performance testing and cycle testing at 60°C. The battery retained 88% of its capacity after 500 cycles, indicating that the composite diaphragm has excellent high temperature stability and chemical stability.
[0194] Therefore, it can be seen from the above experimental data that the sodium ion battery prepared using the composite membrane of the present invention shows significant advantages in high power, high energy density and long cycle life, and can meet the application requirements of high-performance sodium ion batteries.
Claims
1. A method for manufacturing a ceramic composite diaphragm, characterized in that: The method comprises the following steps: (1) mixing at least two of a rare earth oxide, a metal organic framework material, and a glass powder, a polysilazane resin, and an organic solvent to obtain a precursor slurry, wherein the polysilazane resin comprises a hyperbranched polysilazane resin; (2) electrospinning the precursor slurry to obtain a precursor film; (3) The precursor film is subjected to UV cross-linking, plasma treatment and curing treatment in sequence to obtain the ceramic composite diaphragm.
2. The method according to claim 1, characterized in that The polysilazane resin further comprises at least one of perhydropolysilazane resin, polyborosilazane resin, polyaluminosilazane resin, polyzirconium silazane resin, and polytitanium silazane resin, or a combination thereof, more preferably a combination of hyperbranched polysilazane resin, polyborosilazane, and polyaluminosilazane.
3. The method according to claim 1, characterized in that The structural formula of the hyperbranched polysilazane resin is: n=3 to 240, preferably n=60 to 240; and / or, the average molecular weight of the hyperbranched polysilazane resin is 2,000 to 200,000, preferably 10,000 to 200,000, more preferably 50,000 to 200,000; And / or, the hyperbranched polysilazane resin, as measured by TG / DSC, is heated to 1350° C. at a rate of 5-20° C. / min under a nitrogen atmosphere, and has a total weight loss rate of ≤30 wt % at ≤700° C., and a weight loss rate of ≤5 wt % between 700° C. and 1350° C.
4. The method according to claim 1, wherein The rare earth oxide is selected from at least one of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, and Gd2O3, or a combination thereof, preferably at least two or at least three of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, and Gd2O3; and / or, the content of rare earth oxide in the precursor slurry is 0.1 to 1.2 wt %, preferably 0.5 to 1.2 wt %; And / or, the average particle size of the rare earth oxide is 10 nm to 100 nm.
5. The method according to claim 1, wherein The metal organic framework material is at least one of silicon nanorods @ SWCNT core-shell MOF structural material, MIL-101 material (chromium-based MOF), UiO-66 (zirconium-based MOF), MOF-74 (magnesium-based MOF) and MOF-5 (zinc-based MOF) or a combination thereof; And / or, the average particle size of the metal organic framework material is 100 nm to 300 nm; And / or, the content of the metal organic framework material in the precursor slurry is 3-8 wt %.
6. The method according to claim 5, characterized in that The silicon nanorod@SWCNT core-shell MOF structure material has a SWCNT diameter of 80±5 nm and a silicon nanorod shell thickness of 10 nm; and / or The specific surface area of the MIL-101 material is 3000m 2 / g, and the pore size is 2 to 3 nm.
7. The method according to claim 1, characterized in that The glass powder is selected from at least one of low-temperature glass powder, medium-temperature glass powder and high-temperature glass powder, or a combination thereof; And / or, the content of glass powder in the precursor slurry is 3-8 wt%; Preferably, the glass powder is nano glass powder, and more preferably the particle size of the nano glass powder is 50 to 500 nm; Preferably, the melting point of the low-temperature glass powder is 500-600°C, the melting point of the medium-temperature glass powder is >600-800°C, and the melting point of the high-temperature glass powder is >800°C-1300°C.
8. The method according to claim 1, characterized in that The content of the polysilazane resin in the precursor slurry is 25 to 75 wt %, preferably 25 to 55 wt %, and more preferably 35 to 50 wt %; And / or, the viscosity of the precursor slurry is 350±20 cP (25° C.), and the Zeta potential is greater than +30 mV.
9. The method according to claim 1, characterized in that The electrospinning is carried out under the following conditions: the propulsion speed of the precursor slurry is 0.5-2.0 mL / h, the voltage is 15-25 kV, the distance between the electrospinning receiving device and the nozzle is 10-20 cm, the ambient temperature is 20-30° C., and the relative humidity is 30%-50%; And / or, the precursor membrane is a nanofiber membrane formed by three-dimensional interweaving of nanofibers, and the diameter of the nanofibers is 60 to 800 nm, preferably 150±20 nm.
10. The method according to claim 1, characterized in that The ultraviolet crosslinking comprises: immersing the precursor film in a crosslinking agent solution, taking it out and drying it, and then irradiating it with ultraviolet light to obtain a crosslinked precursor film; Preferably, the crosslinking agent in the crosslinking agent solution is selected from at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate, or a combination thereof; Preferably, the wavelength of the ultraviolet light irradiation is 200-370nm, the power is 10-30W, and the irradiation time is 10-80 minutes; more preferably, the ultraviolet light irradiation is first performed at a wavelength of 254nm and a power of 10-20W for 20-30 minutes, and then at a wavelength of 222nm and a power of 10-20W for 20-30 minutes.
11. The method according to claim 1, wherein The plasma treatment is carried out under the following conditions: power of 50 to 100 W, gas pressure of 0.1 to 0.5 Pa, and time of 10 to 20 minutes; And / or, the curing treatment is carried out under the following conditions: temperature of 150 to 800° C. and time of 6 to 10 hours; Preferably, the curing treatment includes: first keeping warm at 150-200°C for 1-2 hours, then heating to 250-300°C and keeping warm for 2-3 hours, finally heating to 350-400°C and keeping warm for 3-4 hours, and finally optionally keeping warm at >400-600°C for 2-3 hours.
12. The method according to claim 1, characterized in that The method further comprises a step (4) after step (3): subjecting the ceramic composite diaphragm to a laser cracking treatment or a microwave curing treatment; the atmosphere of the laser cracking treatment is a non-oxidizing atmosphere, preferably a vacuum atmosphere or an inert atmosphere.
13. A ceramic composite diaphragm, characterized in that: The ceramic composite membrane is a nano-ceramic fiber membrane, which is three-dimensionally interwoven with nano-ceramic fibers composed of at least two of rare earth oxides, glass powders and metal-organic framework materials and a ceramic phase, wherein the rare earth oxides and glass powders are dispersed in the ceramic phase, and the metal-organic framework material and the ceramic phase form a composite structure; preferably, the ceramic phase is formed by a cross-linking reaction between a polysilazane resin and a cross-linking agent, and more preferably, the ceramic phase contains at least one of SiCN, Si3N4, SiC or a combination thereof.
14. The ceramic composite diaphragm according to claim 13, characterized in that: The diameter of the nano-ceramic fibers in the ceramic composite diaphragm is 50 to 600 nm; And / or, the content of the ceramic phase is 60-80 wt %, preferably, the amorphous ceramic phase in the ceramic phase accounts for 60-100% of the total mass of the ceramic phase; and / or, the content of the rare earth oxide is 1 to 3 wt %, preferably, the rare earth oxide is selected from at least one of Sc2O3, Sm2O3, La2O3, CeO2, Y2O3, CeO2, Nd2O3, Eu2O3, Gd2O3 or a combination thereof, preferably a combination of Sc2O3, Sm2O3 and La2O3; And / or, the content of the metal organic framework material is 5 to 20 wt %, and the metal organic framework material is selected from at least one of silicon nanorods @ SWCNT core-shell MOF structural material, MIL-101 material (chromium-based MOF), UiO-66 (zirconium-based MOF), MOF-74 (magnesium-based MOF) and MOF-5 (zinc-based MOF) or a combination thereof, preferably silicon nanorods @ SWCNT core-shell MOF structural material; And / or, the content of the glass powder is 5 to 20 wt %, and the glass powder is selected from at least one of low-temperature glass powder, medium-temperature glass powder, and high-temperature glass powder, or a combination thereof; the glass powder is nano-glass powder, and more preferably, the particle size of the nano-glass powder is 50 to 500 nm; preferably, the melting point of the low-temperature glass powder is 500 to 600° C., the melting point of the medium-temperature glass powder is >600 to 800° C., and the melting point of the high-temperature glass powder is >800 to 1300° C.; and / or, the cross-linking agent is selected from at least one of divinylbenzene, diacrylate, 1,6-hexanediol diacrylate, ethylene glycol dimethacrylate, and pentaerythritol tetraacrylate, or a combination thereof; And / or, the polysilazane resin comprises a hyperbranched polysilazane resin, preferably further comprises at least one of a perhydropolysilazane resin, a polyborosilazane resin, a polyaluminosilazane resin, a polyzirconium silazane resin, and a polytitanium silazane resin, or a combination thereof, more preferably a combination of a hyperbranched polysilazane resin, a polyborosilazane, and a polyaluminosilazane.
15. The ceramic composite diaphragm according to claim 13, characterized in that: The ceramic composite diaphragm satisfies one or more of the following characteristics: The ceramic composite diaphragm has a temperature resistance limit of ≥390°C, preferably ≥410°C, with a shrinkage rate of no more than 1.5% as measured according to ISO 11359; The ionic conductivity of the ceramic composite diaphragm measured according to ASTM D257 standard is ≥1.2 mS / cm, preferably ≥1.8 mS / cm; The ceramic composite diaphragm has a tensile strength measured according to ASTM D638 of ≥170 MPa, preferably ≥200 MPa; The porosity of the ceramic composite diaphragm measured according to ISO 9277 standard is 75-90%, preferably 80-90%; The ceramic composite diaphragm has an operating temperature of -60°C to 1350°C.
16. A battery, characterized in that: The battery comprises the ceramic composite diaphragm according to claim 13; preferably, the battery comprises a sodium ion battery, a lithium ion battery and a sulfur ion battery.
17. Use of the ceramic composite diaphragm according to claim 13 or the battery according to claim 16 in energy storage power stations, aircraft, ships, and automobiles.
Citation Information
Patent Citations
Electrospinning technique-based ceramic diaphragm and preparation method thereof
CN106638007A
Heat-resistant flame-retardant composite diaphragm as well as preparation method and application thereof
CN114583383A
Cited By
Electrically controlled drug release metal organic framework based composite application as well as preparation method and application thereof
CN121371235A